A map of the world from the best authorities. - Guthrie, William, 1708-1770 (C. Dilly & G. Robinson, 1785)
Map shows the exploration routes of Captain James Cook through 1780; six continents [Australia as New Holland], political boundaries, and major cities; Arctic portion of North America and some South Pacific coastlines as vague or incomplete; notes in Antarctic vicinity. Includes explanation of Captain Cook's routes and notes. Relief shown pictorially. Scale not indicated.